2018
DOI: 10.16965/ijar.2018.341
|View full text |Cite
|
Sign up to set email alerts
|

A Morphometric Study of the Thyroid Gland in Human Cadavers

Abstract: The size and shape of the thyroid gland may alter remarkably with age, gender, physiological condition, race, and geographical location. Thus the knowledge of the various parameters and position of thyroid gland are important while doing surgeries on thyroid gland as well as during tracheostomy in emergency condition. Materials and methods:The study was structured to investigate the morphometric as well as topographical features of the thyroid gland in 100 cadavers (58 males and 42 females) from Maharashtrian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…However, a study done by Raut et al, (2018) found a higher incidence of LGT (38.33%) than PL (25%). Geographical location and ethnicity could have contributed to differences in statistics (Gaikwad and Joshi, 2018). In our study, there was a high incidence of PL in males (36.1%) than females (20%).…”
Section: Discussionmentioning
confidence: 52%
“…However, a study done by Raut et al, (2018) found a higher incidence of LGT (38.33%) than PL (25%). Geographical location and ethnicity could have contributed to differences in statistics (Gaikwad and Joshi, 2018). In our study, there was a high incidence of PL in males (36.1%) than females (20%).…”
Section: Discussionmentioning
confidence: 52%